Pomiar warunków i preferencji mieszkaniowych emerytów - Foryś, Iwona (The Measurement of Housing Conditions and Preferences of Pensioners, 2009)
The article presents the results of a survey concerning housing conditions and preferences of pensioners. The author uses basic statistical measures, the Ward method and the AHP method to establish the hierarchy in profiles. To estimate the average usefulness of partial levels of attributes, the author uses the multiple regression model. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 248-255